On the Problem of Rational Use of the Potential of the Natural and Cultural Heritage of the Crimea: Features of Development Based on the Concept of a Unique Historical Territory - Nikolay V. Nikolaenko (Publishing house "Sreda", 2022)
The article is devoted to the problem of rational use of the potential of natural and cultural heritage objects. The relevance of the article is due to the fact that the development of Crimean tourism and local history organizations urgently requires practical measures to modernize socio- and ethno-cultural activities, and also leads to the search for new forms of interaction with local museums and the development of innovative methods and principles of preserving cultural and historical heritage. The author of the article considers the ecomuseum project "Belbek Valley" as an opportunity to reconstruct the appearance of rural dwellings of the 8-9 centuries. He raises the question of the materialization of such a reconstruction, the creation of a museum complex that will clearly present an early medieval rural settlement. The purpose of the article is to give an idea of the initial stage of design, i.e. the identification of the main objects of the prospective territory of the Crimea, followed by the development of a comprehensive program for the development of the region on the principles of the concept of unique historical territories. The materials for the study were natural monuments, archaeological sites, medieval historical and cultural memorials of the Crimean Peninsula. Based on the method of theoretical analysis, the uniqueness of the ecomuseum project "Belbek Valley" was substantiated. The conclusion of the article is made about the mountainous southwestern part of the Crimean Peninsula as a unique territory, which is a holistic, dispersed museum, full of monuments of nature, history, and culture.